The principal's guide to a powerful library media program - McGhee, Marla W.; Jansen, Barbara A. (Gale virtual reference library, 2005)
A handbook that describes a specific collaborative process for library media specialists and classroom teacher to use in planning teaching units. Written for K-12 educators. Also provides suggested book lists, websites, and professional resources.